O-010 Planning for Efficiency: Survey of Technical and Workflow Practices before Mechanical Thrombectomy. (29th July 2016) - Kansagra, A; Meyers, G; Kruzich, M; Cross, D; Moran, C; Derdeyn, C
Abstract : Background: Mechanical thrombectomy plays a critical role in the management of acute ischemic stroke due to emergent large vessel occlusion (ELVO). As healthcare systems adapt to more efficiently deliver patients with ELVO for timely thrombectomy, hospitals may benefit from increased awareness of successful workflows in place at other centers experienced with endovascular intervention. Methods: E-mail and phone interviews were conducted with endovascular team members at each of 30 high volume stroke centers. Each of these centers was certified as an Advanced Comprehensive or Advanced Primary Stroke Center. Questions were categorized into four major workflow steps of triage, team activation, transport, and case preparation. Results: During the triage workflow step, 53% of surveyed institutions designate specific non-physician staff to respond to stroke alerts alongside physicians and facilitate timely triage. Imaging triage involves CT angiography and CT perfusion at 57% of institutions, CT angiography without CT perfusion at 30%, and some use of MRI at 10%. During the team activation step, the neurointerventionalist was contacted prior to completion of non-invasive imaging at 86% of institutions, and thus before triage was a decision to treat could be made. Likewise, the remaining neurointerventional team members were called in prior to making a decision to treat at 59% of institutions. Team members were contacted directly by the neurointerventionalist at 63% of institutions, and by a hospital operator at 23%. Once activated, the mean required arrival time for nurse and technologist staff was 30 minutes. During the transport workflow step, patients were permitted to be transported to the neurointerventional suite before team arrival at 43% of institutions. Emergency department staff were involved in transport at 87% of facilities, while the neurointerventional team was involved at only 20%. For the case preparation step, procedural trays were set up in advance of team arrival at only 13% of institutions. Thrombectomy devices were stored in a centralized, easy-to-find location at 54% of centers. A power injector for angiographic runs was consistently used at 43%, but no institution left the injector loaded in anticipation of cases. Anesthesiology routinely participated in thrombectomies at 67% of institutions, though general anesthesia was only used consistently in only 21%. Conclusion: Workflow processes related to triage, team activation, transport, and case preparation prior to mechanical thrombectomy vary widely between institutions. These differences may reflect institution-specific factors or incomplete awareness of best practices. Broader dissemination of best practices and successful workflows may allow institutions to develop more efficient systems of care than would otherwise be possible. Disclosures: A. Kansagra: None. G. Meyers: None. M. Kruzich: None. D. Cross: None. C. Moran: 2; C; Medtronic Neurovascular. 3; C; Medtronic Neurovascular. C. Derdeyn: None.